2017
DOI: 10.1038/npp.2017.112
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 Receptor Signaling in the Nucleus Accumbens Comprises a Metabolic–Cognitive Brain Interface Regulating Metabolic Components of Glucose Reinforcement

Abstract: Appetitive drive is influenced by coordinated interactions between brain circuits that regulate reinforcement and homeostatic signals that control metabolism. Glucose modulates striatal dopamine (DA) and regulates appetitive drive and reinforcement learning. Striatal DA D2 receptors (D2Rs) also regulate reinforcement learning and are implicated in glucose-related metabolic disorders. Nevertheless, interactions between striatal D2R and peripheral glucose have not been previously described. Here we show that man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
2
9
0
1
Order By: Relevance
“…Glucose tolerance refers to the clearing of glucose from the bloodstream after a meal or glucose administration, while glucose intolerance reflects an inability or delay in the clearance of elevated blood glucose 28 . Our finding that D2R-OE NAc mice exhibit glucose intolerance is consistent with recent evidence suggesting that striatal dopamine regulates energy homeostasis 28 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose tolerance refers to the clearing of glucose from the bloodstream after a meal or glucose administration, while glucose intolerance reflects an inability or delay in the clearance of elevated blood glucose 28 . Our finding that D2R-OE NAc mice exhibit glucose intolerance is consistent with recent evidence suggesting that striatal dopamine regulates energy homeostasis 28 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Glucose tolerance refers to the clearing of glucose from the bloodstream after a meal or glucose administration, while glucose intolerance reflects an inability or delay in the clearance of elevated blood glucose 28 . Our finding that D2R-OE NAc mice exhibit glucose intolerance is consistent with recent evidence suggesting that striatal dopamine regulates energy homeostasis 28 , 46 , 47 . In particular, Michaelides et al (2017) recently showed that mice lacking dopamine- and cAMP-regulated neuronal phosphoprotein (DARPP-32) exclusively in D2R-expressing cells exhibit glucose intolerance and upregulation of D2R mRNA selectively in the NAc 28 , and that direct infusion of the D2R agonist bromocriptine into the NAc of normal mice increases glucose intolerance 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D2R is involved not only in schizophrenia, but also in elevated levels of blood glucose in schizophrenic patients (Lawford et al., 2016). Glucose modulates striatal dopamine in mice, whereas striatal D2R regulates peripheral glucose levels and is implicated in glucose‐related metabolic disorders (Michaelides et al, 2017). Mice lacking D2R are glucose intolerant and have abnormal insulin secretion (Lopez Vicchi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…whereas striatal D2R regulates peripheral glucose levels and is implicated in glucose-related metabolic disorders (Michaelides et al, 2017). Mice lacking D2R are glucose intolerant and have abnormal insulin secretion (Lopez Vicchi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%